Peningkatan Hasil Belajar Siswa Sekolah Dasar Menggunakan Model Make a Macth - Akbar, Andri Hayatul; Desyandri, Desyandri (Universitas Negeri Padang, 2021)
This research is motivated by the less optimal of integrated thematic learning which the students is not understanding the material, so that it impacts on learning outcomes. This research have purpose to describe the Improvement of Integrated Thematic Learning Outcomes which it isusing the Make A Macth Model Model for Grade IV Students at SDN 36 Cengkeh Padang City. This research use methodology PTK with qualitative and quantitative approaches. This Research get data in the form of observations, tests and non-tests. Theis reasearch is conducted in two cycles. The Research subjects are teachers and grade IV students. The results showed the average on cycle one 90.62%, it increased in the second cycle 100%, that is excellent . The implementation of learning aspects of the first cycle teacher got average 81.25% in good quality, it increased in the second cycle to be exelelent at 96.87%. Aspects of the first cycle students got average 76.56% in fair quality it increased in the second cycle to excellent at 96.87% . Learning outcomes in the first cycle obtained an average of 68.22 in fair quality, it increased in the second cycle with an average value of 88.33%, excellent.